2017
DOI: 10.1007/s12253-017-0188-4
|View full text |Cite
|
Sign up to set email alerts
|

miR-10b, miR-26a, miR-146a And miR-153 Expression in Triple Negative Vs Non Triple Negative Breast Cancer: Potential Biomarkers

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs composed of 18-25 nucleotides that can post-transcriptionally regulate gene expression and have key regulatory roles in cancer, acting as both oncogenes and tumor suppressors. About 1000 genes in humans encode miRNAs, which account for approximately 3% of the human genome, and up to 30% of human protein coding genes may be regulated by miRNAs. The objective of this article is to evaluate the expression profile of four miRNAs previously implicated in triple negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…10 Fkih M'hamed et al have found that the expression levels of miR-153 in TNBC and non-TNBC were similar. 33 Nevertheless, another study suggested that the expression of miR-153 was different in diverse molecular types. Compared with Luminal A, Luminal B and HER-2 positive breast cancer, the expression of miR-153 was lower in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…10 Fkih M'hamed et al have found that the expression levels of miR-153 in TNBC and non-TNBC were similar. 33 Nevertheless, another study suggested that the expression of miR-153 was different in diverse molecular types. Compared with Luminal A, Luminal B and HER-2 positive breast cancer, the expression of miR-153 was lower in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, HER2 and HER3 (erbB3), which are significantly correlated with decreased disease-specific survival in breast cancer patients, could be suppressed by miR-125a or miR-125b [ 34 ]. MiRNAs’ role in TNBC also has been discovered, for instance, the miR-146a and miR-26a were reported over-expressed in triple negative breast cancer and miR-10b and miR-153 were significantly associated to lymph node metastases occurrence in TNBC [ 35 ]. These results highlighted the role of miRNAs in breast cancer research.…”
Section: Discussionmentioning
confidence: 99%
“…This expression pattern in basal‐like cells was also observed by Sandhu et al (), who found that antagomiR‐mediated knockdown of miR‐146a resulted in decreased proliferation and promotion of apoptosis, despite loss of p53 in these cells. Overexpression of miR‐146a was observed in triple negative breast cancer cases and positively correlated with lymph node metastasis (Fkih M'hamed et al, ). Increased miR‐146a expression in breast cancer was also seen by Wang et al (), who identified the Notch pathway inhibitor NUMB as a target.…”
Section: Role Of Mir‐146a In Specific Cancersmentioning
confidence: 99%